"Transparência": produção e circulação de uma fórmula discursiva do neoliberalismo - Damaceno, Livia Beatriz (Universidade Federal de São Carlos, 2020)
This research is carried out within the scope of the French discourse analysis (according to the discipline's current guidelines, discussed, among others, in MAINGUENEAU, 2015) about the term “transparency”, which we hypothesized to be a discursive formula for meeting, in its current circulation , to the properties proposed by the theory of Krieg-Planque (2010), which are: to be a crystallized formal structure, to function in a discursive dimension, to have a controversial character and to establish itself as a social referent. The theme investigated in the research is important for understanding part of the current political situation, as it materializes in different social groups, considering that, in the data observed preliminarily, “transparency” is often placed as a condition for the functioning institutions. The survey of the occurrences of the term and its variants (such as, for example, “transparent”) occurs through the notion of route (MAINGUENEAU, 2015). The collection of occurrences is made from the Google applications (Google Search, Google Trends, Google Alerts), from the DuckDuckGo search engine, in three different internet protocols (IPs) and disconnected from Google accounts, in order to diversify the results, avoiding the personal device bias. The analysis of the senses mobilized by the social actors to understand the discursive dimension and the controversial dimension of the formula, and thus turn to the circulation of that expression, in order to understand a little of the practices that crystallize and, at the same time, are instituted by she. In addition, the discursive functioning of power relations that permeate these practices is explored. That is, the disputes for meaning between institutions and subjects, which occur in a given public space and at a given time, the way in which subjectivities adapted to the production and acceptance of neoliberal politics and economics are produced. The research concludes that this formula works as a supposed cure for corruption, therefore it has a positive, desirable and unquestionable value, at the same time that it is a vector of demonization of what is not transparent.
"Transparency": production and circulation of a discursive formula of neoliberalism
Keywords: Análise do discurso francesa; Fórmula discursiva; Transparência; Discourse analysis; Discursive formula; Transparency; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA